OBTAINING OF NEW KNOWLEDGE IN CONCERNING «AIR CONDITIONING» AT THE RAILWAY TRANSPORT: SCIENTOMETRIC ASPECT - Kolesnykova, T. O.; Pominova, O. V.; Kolesnykov, S. R. (Science and Transport Progress, 2016)
Purpose. The research aimes at obtaining of new knowledge in «air conditioning» direction development at railway transport using products and services of Web of Science (WoS) scientometric database. Chronological frameworks of the studied scientific articles are – 2010-2015 years. Methodology. In order to obtain relevant empirical data the authors reviewed the world literature on the paper topic with the use of full-texts and abstract databases. The algorithm of «incremental» actions in WoS was considered according to: 1) forming the «core» of publications; 2) establishment of the most «top» issues; 3) identifying the most intellectually productive authors; 4) determining the representation level of thematic publications of Ukrainian scientists in WoS; 5) the presence of collaboration among scientists from different countries on the investigational subject. Findings. The authors proved: 1) climate comfort, energy efficiency and thermal comfort are the top-themes of «air conditioning» direction at railway transport; 2) Ukrainian scientists have not yet joined to the global processes in the thematic scientific information sharing; 3) the most intellectually productive authors of scientific articles are China’s scientists; 4) there is no information about international collaboration of scientists on the investigational subject. Originality. The authors firstly conducted scientometric research in the field of railway transport (subject area «air conditioning») on the basis of products and services in the global WoS citation database. Practical value. Based on the results, one can correct personal exploration research of individual scientists or research teams as well as predict further prospects of the subject «air conditioning» direction at the railway transport. Survey data may also be useful in the study of the «Scientific information system and scientometrics» subject, organization of workshops, training courses, etc.